Calcium-sensor proteins but not bicarbonate ion activate retinal photoreceptor membrane guanylyl cyclase in photoreceptors - Peshenko, Igor V.; Olshevskaya, Elena V.; Dizhoor, Alexander M. (Frontiers in Molecular Neuroscience, 2024)
Retinal membrane guanylyl cyclase (RetGC), regulated by guanylyl cyclase activating proteins (GCAPs) via negative calcium-feedback, is one of the most critically important enzymes in vertebrate rod and cone physiology, enabling their sensitivity to light. It was also reported that, similarly to olfactory receptor guanylyl cyclase, bicarbonate anion directly stimulates RetGC activity in photoreceptors as a novel phototransduction-linked regulating factor. We directly tested whether or not RetGC is a bicarbonate-activated enzyme using recombinant human RetGC expressed in HEK293 cells and the native RetGC in mouse retinas. Whereas RetGC in all cases was activated by GCAPs, we found no evidence indicating that bicarbonate can produce direct stimulating effect on RetGC catalytic activity, either basal or GCAP-activated, even at concentrations as high as 100 mM. Instead, near-physiological concentrations of bicarbonate only slightly reduced RetGC activity, whereas concentrations substantially exceeding physiological levels caused a more pronounced reduction of RetGC activity measured in mouse retinas. Our results argue that photoreceptor guanylyl cyclase is not a bicarbonate-stimulated enzyme and rule out the possibility that effects of bicarbonate on photoreceptor physiology are mediated by a direct stimulation of retinal guanylyl cyclase by HCO3−.